2005
DOI: 10.1152/ajpgi.00444.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acute colitis induction by oil of mustard results in later development of an IBS-like accelerated upper GI transit in mice

Abstract: Oil of mustard (OM) is a potent neuronal activator that promotes allodynia and hyperalgesia within minutes of application. In this study, OM was used to induce an acute colitis. We also investigated whether intracolonic OM-induced inflammation alters gastrointestinal (GI) function over a longer time frame as a model of postinflammatory irritable bowel syndrome (PI-IBS). Mice given a single administration of 0.5% OM developed a severe colitis that peaked at day 3, was reduced at day 7, and was absent by day 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
94
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 41 publications
9
94
0
Order By: Relevance
“…1 Meanwhile, it has been known that MO displays proinflammatory activity mainly via inducing plasma extravasation, which is principally due to the release of substance P and to NK1 receptor activation. [7][8][9][10] These differences in mechanism between the 2 agents may explain in part the lack of GI motility response to SKI3246 in the MO-induced model in this study.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…1 Meanwhile, it has been known that MO displays proinflammatory activity mainly via inducing plasma extravasation, which is principally due to the release of substance P and to NK1 receptor activation. [7][8][9][10] These differences in mechanism between the 2 agents may explain in part the lack of GI motility response to SKI3246 in the MO-induced model in this study.…”
Section: Discussionmentioning
confidence: 82%
“…MO, allyl isothiocyanate, the predominant aromatic constituent of mustard, horseradish, and wasabi, is a direct stimulant of small nerve fibers and a potent acute inflammatory irritant. 7 Although the GI response to MO in guinea pig is not well-documented, the intra-colonic administration of MO in mice results in acute colitis, which may progress to an IBS-like acceleration of upper GI transit. 7 In our guinea pig Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahgoub et al [41] used intracolonic 3% ascetic acid which produced severe colitis 24 hours after administration. Kimball et al [42] used mustard oil that caused a peak inflammation at day 3 and was resolved by day 7. The Natah group found that a quantitative analysis of the endothelial barrier antigen (EBA) after TNBS induced colitis resulted in occluding expression in the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Kimball et al evaluated the effect of selective cannabinoid receptor agonists in a mouse model of accelerated upper gastrointestinal transit resembling post-inflammatory IBS (PI-IBS) (Kimball et al, 2010). The experimental model is generated by intracolonic administration of mustard oil, which induce transient colitis and, in the longer term (i.e., 28 days after mustard oil) a functional increase in gastrointestinal transit that is observed when there is no inflammation (Kimball et al, 2005). It was found that both cannabinoid receptor subtypes were up-regulated in the small intestine, an effect closely associated to increased efficacy of both CB 1 and CB 2 receptor agonists in normalizing the accelerated transit (Kimball et al, 2010).…”
mentioning
confidence: 99%